The BRI and its Implications for China’s energy security: The Four As Model Perspective - Madani, Seyedashkan (International Journal of Energy Economics and Policy, 2021)
The ‘Belt and Road Initiative’ (BRI) proposal provides an opportunity to address the challenges of energy security. This paper aims to explore the relationship between China’s energy policies and the BRI, especially in energy security, by highlighting the energy status in China and its top energy priorities. In this study, the analytical framework presented is based on the model of “four As.” The results indicated that BRI can improve China’s energy security in all four areas of availability, accessibility, affordability, and acceptability. By deepening energy cooperation with BRI countries, the import transportation channels of energy in China can be further diversified, its room for maneuver in the international energy market will increase, along with its voice in international energy negotiations and global energy governance. The initiative will enable member states to collaborate on energy supply and security issues broadly and strategically. In addition, it can improve energy development efficiency and speed up the circulation of investment funds. Further, BRI can increase energy technology exchanges and cooperation with major energy-consuming countries such as Japan and Singapore. Contrary to merely geopolitical analysis, China’s BRI Energy Sustainable Project should be observed in a broader context in terms of sustainable development and economic objectives. Under the framework of the BRI strategy, the future development path of China’s energy security strategy may open the way for pluralistic economic cooperation in the field of energy. Keywords: Energy Security, Energy Strategy, Belt and Road Initiative, BRI, China JEL Classifications: F50; F63; H10 DOI: https://doi.org/10.32479/ijeep.11221